The Use of Odd One Out Game to Improve Students Listening Skill at MTSN 2 Makassar (Karya Ilmiah Mahasiswa (KIMA), 2026)
The purpose of this study is to find out the use of odd one out game in improving students’ listening skills. Odd one out game is a game that allows students to explore and become familiar with words and phrases. This research was conducted in third grade of MTSN 2 Makassar which consisted of 34 students. This research used quantitative method with classroom action research (CAR) approach. In this research, it was found that the mean score in the pre-test was 39.33 and no students reached the standard score, in the first cycles the mean score of students was 69.82 and at least 44% of students reached the standard score, and in the second cycles the mean score of students was 85 and at least 88% of students reached the standard score. Based on the data above , respondents believe that odd one out game can improve students listening skills.